Gender-based violence as a destructive form of warfare against families: A practical theological response - Freeks, Fazel E. (HTS teologiese studies, 2023)
War is an appalling crisis and destructive force on human dignity and life. War was permitted in biblical times at the hand of God, with disastrous consequences for the nations of the Ancient World. The current war between Ukraine and Russia is fast becoming a global catastrophe, with the threat of World War III looming. Warfare destroys families, and families are vital units God instituted in society. The critical issue addressed in this article is the ruining effects of gender-based violence (GBV) on family life. Therefore, this article responds to GBV as a social ill and destructive form of warfare against women and aims to propose feasible, viable, and practical theological ways to curb this ruinous issue. Gender-based violence, as a form of warfare against women and children, is one of the most destructive forces regarding family life and the key reason for unstable, disrupted, and fractured families. Because this article is grounded on a practical theological response, its pastoral role is explored. Practical theology builds a theological framework for critical evaluation. It also takes a more direct role on the moral debates of society on issues such as GBV, father absence, and family violence that occurs in Church, family, and society.Contribution: This article employed a descriptive modus operandi on GBV against women and endorses the journal’s focus on family and society who is experiencing a violation of human rights and a life-threatening issue in the field of Practical Theology.